Analytical modelling of via-associated recombination losses in MWT solar cells. (September 2017) - Razzaq, Arsalan; Chen, Jia; Duerinckx, Filip; Gordon, Ivan; Szlufcik, Jozef; Poortmans, Jef
Abstract: This work focuses on analytical modelling as an alternative to numerical simulations for determining via-related recombination losses in MWT silicon solar cells. Two new analytical models are presented in this framework. The first model deals with calculation of the local via recombination velocity S via from photoconductance lifetime measurements. The second model relates S via to loss in V OC by solving the diffusion equation in two-dimensions. From short-loop tests, we show that these analytical models are valid over a wide range of via densities. The results also show that alkaline etching treatment after the laser via drilling step reduces S via by an order of magnitude and thus allows for good via passivation. We then make use of these models for estimating V OC loss in our MWT solar cells as a result of via recombination. We find that via recombination losses can be substantial at high via densities and so by limiting the number of vias on large area cells (239 cm 2 ) and with good via passivation, the V OC loss can be limited to ~ 1 mV. This finding is in agreement with our cell integration results.